Factors Related to The Mother's Readiness to Face Menopause Bandar Klippa Village, Percut Sei Tuan District, Deli Serdang Regency - Novi Susanti (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2022)
Menopause is the scientific cessation of menstruation. One of the problems in menopause will be caused by the mother's lack of readiness to deal with menopause which can cause symptoms, diseases and psychological disorders that need attention.This type of research is a descriptive-analytical survey using secondary and primary data. This study included all postmenopausal women in hamlet XX, Bandar kalippa Village, Percut Sei Tuan District, Deli Serdang Regency with a sample of 38 people.The results of this study show that the readiness of postmenopausal women to face menopause in 2022, based on the age of the majority of 40-44 years 20 people (52.63%) and based on the majority of junior high school education below 21 people (55.26%) and based on the knowledge that lacks knowledge 28 people (73.68%) and based on the economy 26 people (68.42%). Moreover, this shows that the probability (0.000) < (0.05) Ho is rejected means Ha is accepted; it can be concluded that age, education, knowledge and economy are related to the mother's readiness to face menopause.It is hoped that all postmenopausal women in hamlet XX Bandar kalippa Village, Percut Sei Tuan District, Deli Serdang Regency to increase higher readiness for menopause, increase knowledge of menopause, and increase awareness and willingness to overcome disorders and readiness in menopause to create maternal health in dealing with menopause until the elderly.